Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1186/1471-2407-6-214
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibitors strongly sensitise neuroblastoma cells to TRAIL-induced apoptosis by a caspases-dependent increase of the pro- to anti-apoptotic proteins ratio

Abstract: Background: Neuroblastoma (NB) is the second most common solid childhood tumour, an aggressive disease for which new therapeutic strategies are strongly needed. Tumour necrosis factor-related apoptosis-inducing ligand (TRAIL) selectively induces apoptosis in most tumour cells, but not in normal tissues and therefore represents a valuable candidate in apoptosis-inducing therapies. Caspase-8 is silenced in a subset of highly malignant NB cells, which results in full TRAIL resistance. In addition, despite constit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 38 publications
3
28
1
Order By: Relevance
“…1B, H6CAHA potently repressed the growth of prostate cancer cells (GI 50s 1.77-3.6 mM) but did not exert a significant inhibitory effect in nonmalignant prostate epithelial cells (GI 50s 8.3-10 mM). The data demonstrate that H6CAHA preferentially suppresses prostate cancer cell proliferation, similar with other HDAC inhibitors reported by others (15,16). Under the same experimental condition using 1 mM (GI 30 ) of H6CAHA, prostate cancer cells (PC3) were predominantly accumulated in G1 phase (>70%), demonstrating little impact on nonmalignant cells (RWPE1 ; Table S1).…”
Section: H6caha Suppresses the Growth Of Prostate Cancer Cells And Exsupporting
confidence: 84%
“…1B, H6CAHA potently repressed the growth of prostate cancer cells (GI 50s 1.77-3.6 mM) but did not exert a significant inhibitory effect in nonmalignant prostate epithelial cells (GI 50s 8.3-10 mM). The data demonstrate that H6CAHA preferentially suppresses prostate cancer cell proliferation, similar with other HDAC inhibitors reported by others (15,16). Under the same experimental condition using 1 mM (GI 30 ) of H6CAHA, prostate cancer cells (PC3) were predominantly accumulated in G1 phase (>70%), demonstrating little impact on nonmalignant cells (RWPE1 ; Table S1).…”
Section: H6caha Suppresses the Growth Of Prostate Cancer Cells And Exsupporting
confidence: 84%
“…Notably, HDIs and TRAIL also synergistically aVected mitochondrial function in WE-68 cells, indicating that the activities of HDIs and TRAIL converge upstream of mitochondria. Increased sensitivity to TRAIL may stem from elevated expression of TRAIL receptors (Guo et al 2004;Nakata et al 2004;Chopin et al 2004;Singh et al 2005;Earel et al 2006), though the cooperation of HDIs and TRAIL has not always been found to be associated with increased TRAIL receptor expression (Rosato et al 2003;Muhlethaler-Mottet et al 2006). In SK-ES-1 and WE-68 cells, HDIs did not upregulate TRAIL receptors, in fact, we observed a slight reduction of TRAIL-R2 cell surface exposure.…”
Section: Discussionmentioning
confidence: 58%
“…In several tumour types, TRAIL activity could be ampliWed by cotreatment with HDIs. For example, coadministration of HDIs increased the killing eYciency of TRAIL in leukaemia cells (Rosato et al 2003;Guo et al 2004;Nakata et al 2004), in colon carcinoma cells (Inoue et al 2002), breast cancer cells (Chopin et al 2004;Singh et al 2005), in lung and prostate cancer cells (Sonnemann et al 2005), in bladder cancer cells (Earel et al 2006) and in neuroblastoma cells (Muhlethaler-Mottet et al 2006). In this study, we have demonstrated that HDIs and TRAIL synergised to induce apoptosis in WE-68 cells.…”
Section: Discussionmentioning
confidence: 70%
“…46 Additional support for the feasibility of this combination has been described in adults with solid tumors and non-Hodgkin lymphoma. 47 Moreover, it has been shown in previous studies that apoptosis induced by these epigenetic agents is specific to the malignant cell population and has comparatively little or no activity against their normal counterparts (nonmalignant cells), [48][49][50] suggesting that incorporating these agents episodically in the standard reinduction chemotherapy for the treatment of relapsed ALL is feasible.…”
Section: Discussionmentioning
confidence: 99%